Prospective multicentre randomised controlled trial to assess the clinical effectiveness of the novel CirrhoCare digital therapeutic management system: a study protocol - Rajeshwar P Mookerjee; Rajiv Jalan; Olivia Greenham; Kohilan Gananandan; Zia Sadique; Konstantin Kazankov; RAVI KUMAR; Anu Balaji; Maruthi Raja; Ravan Boddu; Jonathan Bamber; Karen L Thomsen; et al. (BMJ Open)
Introduction Liver cirrhosis accounts for over 10 000 deaths in the UK each year with a total loss of 60 000 quality-adjusted life-years. There is a substantial cost to the NHS of £4.5 billion, with new liver-related decompensation events accounting for the majority of this. Following an acute cirrhosis decompensating event, there is a significant risk of hospital readmission with 90-day readmission rates as high as 53%. Current care in the UK is reactive and patients are often only readmitted when they have presented acutely as an emergency with significant decompensation.Methods and analysis CirrhoCare is a prospective, multicentre, randomised controlled trial comparing the CirrhoCare management system with standard-of-care for high-risk cirrhosis patients who have been discharged following an admission with acute decompensation. The CirrhoCare management system comprises a novel digital platform for use in a patient’s home, designed to proactively detect the first signs of new decompensation in patients with established cirrhosis, discharged to the community. This enables a clinician to instigate early community-based care or, if needed, to triage the patient for hospital interventions.214 patients will be recruited to the CirrhoCare trial from at least 12 UK centres. Patients will be randomised on a 1:1 ratio allocation to the CirrhoCare Management System or standard of care. Participants who are randomised to CirrhoCare will receive a CirrhoCare health kit comprising a smart watch, smart phone with enabled SIM (Subscriber Identity Module) network card, blood pressure monitor, weighing scales and thermometer. Participants will take measurements every morning Monday to Friday and will be followed up for 90 days postdischarge.The primary objective of this study is to assess the clinical effectiveness of the CirrhoCare digital management system. We hypothesise that its early community-based intervention will reduce the number of unplanned hospital interventions and admissions and prevent liver-related complications when compared with standard-of-care management.Ethics and dissemination CirrhoCare is a National Institute for Health and Care Research-funded study (NCT06223893). The study has UK Research Ethics Committee and Health Research Authority (HRA) approvals, with approval granted by the HRA and Health and Care Research Wales committee. The results of this study will be published in peer review journals, disseminated at international conferences as well as established Patient and Public Involvement and Engagement networks.Trial registration number ISRCTN11380842.